Oxygen-saturation-related functional parameter as a biomarker for diabetes mellitus—extraction method and clinical validation - Zhang, Jinze; Luo, Zhongzhou; Wang, Gengyuan; Huang, Yuancong; Fei, Keyi; Liu, Yushuang; Li, Jiaxiong; Yuan, Jin; Xiao, Peng (Frontiers in Cell and Developmental Biology, 2023)
Purpose: To develop a computational method for oxygen-saturation-related functional parameter analysis of retinal vessels based on traditional color fundus photography, and to explore their characteristic alterations in type 2 diabetes mellitus (DM). Methods: 50 type 2 DM patients with no-clinically detectable retinopathy (NDR) and 50 healthy subjects were enrolled in the study. An optical density ratio (ODR) extraction algorithm based on the separation of oxygen-sensitive and oxygen-insensitive channels in color fundus photography was proposed. With precise vascular network segmentation and arteriovenous labeling, ODRs were acquired from different vascular subgroups, and the global ODR variability (ODRv) was calculated. Student t-test was used to analyze the differences of the functional parameters between groups, and regression analysis and receiver operating characteristic (ROC) curves were used to explore the discrimination efficiency of DM patients from healthy subjects based on these functional parameters. Results: There was no significant difference in the baseline characteristics between the NDR and healthy normal groups. The ODRs of all vascular subgroups except the micro venule were significantly higher (p<0.05, respectively) while ODRv was significantly lower (p<0.001) in NDR group than that in healthy normal group. In the regression analysis, the increased ODRs except micro venule and decreased ODRv were significantly correlated with the incidence of DM, and the C-statistic for discrimination DM with all ODR is 0.777 (95% CI 0.687-0.867, p<0.001) Conclusion: A computational method to extract the retinal vascular oxygen-saturation-related optical density ratios (ODRs) with single color fundus photography was developed, and increased ODRs and decreased ODRv of retinal vessels could be new potential image biomarkers of DM.